Market Reaction to the Launch of IQOS Iluma at PT Hanjaya Mandala Sampoerna. Tbk - Muchtar, Ali Masjono; Putri, Era Saskia (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2024)
The occurrence of Covid-19 and the increase in cigarette excise rates caused a decline in HMSP share performance over the past three years, resulting in PT Hanjaya Mandala Sampoerna Tbk creating and launching IQOS ILUMA, an innovative smoke-free tobacco product. This launch is expected to generate a positive market reaction so that HMSP's shares have the potential to increase however, market reaction do not always give a positive reaction. Therefore, this study aims to find out whether the existence of IQOS ILUMA can give a positive or negative reaction or even no reaction to HMSP shares. In this study, Researcher will compare market reactions according to the theory of event studies and in real terms. According to the event study theory, market reaction is measured by abnormal returns, and trading volume activity, these is tested by paired sample t-test. Meanwhile, if seen in real terms, it is measured from the price and trading volume of HMSP shares. According the event study theory , the result shows that the launch of IQOS ILUMA did not cause a market reaction to HMSP shares. But in real market, it shows that the launch of IQOS ILUMA gave a positive market reaction to HMSP shares. Keywords: Market Reaction; Event Study; Abnormal Return; Trading Volume Activity; IQOS ILUMA.